SARS-CoV-2 membrane glycoprotein M antagonizes the MAVS-mediated innate antiviral response - Fu, Yu-Zhi; Wang, Su-Yun; Zheng, Zhou-Qin; Yi Huang; Li, Wei-Wei; Xu, Zhi-Sheng; Wang, Yan-Yi (Cellular & molecular immunology, 2021)
A novel SARS-related coronavirus (SARS-CoV-2) has recently emerged as a serious pathogen that causes high morbidity and substantial mortality. However, the mechanisms by which SARS-CoV-2 evades host immunity remain poorly understood. Here, we identified SARS-CoV-2 membrane glycoprotein M as a negative regulator of the innate immune response. We found that the M protein interacted with the central adaptor protein MAVS in the innate immune response pathways. This interaction impaired MAVS aggregation and its recruitment of downstream TRAF3, TBK1, and IRF3, leading to attenuation of the innate antiviral response. Our findings reveal a mechanism by which SARS-CoV-2 evades the innate immune response and suggest that the M protein of SARS-CoV-2 is a potential target for the development of SARS-CoV-2 interventions.